Analisa Sosial Ekonomi Penggunaan Pestisida dalam Usahatani Padi - Delima A. Darmawan; Yusmichad Yusdja; Adreng Purwoto; Chaerul Saleh (Jurnal Agro Ekonomi, 1994)
The Program of Integrated of Pest Management (IPM) play the important role in to decrease the pesticides used in agriculture production. Meanwhile, the farmer has popular known that pesticides was a better solution to face the pest problem. The main objective of this study is to examine the impact of IPM on production and the farmer income. The data was taken from the survey conducted in 1992 in East Sumatera, West Java, Central Java, East Java and North Sulawesi. The result showed that the using of pesticides is still the significance way to protect plant from pest. The research has also shown that around 32 percent of cost was used for pesticides. Several economic factors that have influence on IPM adoption was describe in this report.